2013
DOI: 10.1016/j.jcin.2013.01.128
|View full text |Cite
|
Sign up to set email alerts
|

2-Year Results of Paclitaxel-Eluting Balloons for Femoropopliteal Artery Disease

Abstract: PEBs are associated with favorable functional and clinical outcomes at 2 years in patients with femoropopliteal artery disease requiring percutaneous revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…Longer term outcomes of international DCB registries have shown that the occurrence of restenosis after DCB angioplasty for de novo disease increases by 50% between 12 and 24 months. 62 A similar catch-up phenomenon has also been described after DCB angioplasty to treat ISR after SFA stenting. 63 Cautious optimism is needed to temper the enthusiasm associated with this technology.…”
Section: Drug-coated Balloonsmentioning
confidence: 64%
“…Longer term outcomes of international DCB registries have shown that the occurrence of restenosis after DCB angioplasty for de novo disease increases by 50% between 12 and 24 months. 62 A similar catch-up phenomenon has also been described after DCB angioplasty to treat ISR after SFA stenting. 63 Cautious optimism is needed to temper the enthusiasm associated with this technology.…”
Section: Drug-coated Balloonsmentioning
confidence: 64%
“…of 24 months (1,2,5,8). Available angiography and duplex sonography data were used to determine the binary restenosis rate.…”
mentioning
confidence: 99%
“…Based on a systematic literature review of clinical measures 17 , 12 publications including registries and clinical trials were used to estimate the TLR rates associated with each endovascular procedure studied [19][20][21][22][23][24][25][26][27][28][29]. More detailed information about TLR probabilities indicated in each study is shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%